International politics of the Persian Gulf - Kamrava, Mehran, 1964- (Modern intellectual and political history of the Middle East., 2011)
"For much of the contemporary history of the Middle East, the Persian Gulf has stood at the center of the region's strategic significance. At the same time, the Gulf has been wracked by political instability and tension. Together, the essays in this volume present a comprehensive, detailed, and accessible account of the international politics of the region. Focusing on the key factors that give the Persian Gulf its strategic significance, contributors look at the influence of vast deposits of oil and natural gas on international politics, the impact of the competing centers of power of Iran and Saudi Arabia, the nature of relationships among countries within the Persian Gulf, and the evolving interaction between Islam and politics. Throughout the collection, issues of internal and international security are shown to be central."